Diagnosis and treatment of chronic lymphocytic leukemia: 2025 recommendations of the Brazilian Group of Chronic Lymphocytic Leukemia of the Brazilian Association of Hematology and Hemotherapy (ABHH) - Chiattone, Carlos Sérgio; Marques, Fernanda de Morais; Buccheri, Valeria; Yamamoto, Mihoko; Fortier, Sergio Costa; Ikoma-Colturato, Maura Rosane Valerio; Hamerschlak, Nelson; Figueiredo, Vera Lucia de Piratininga; Silveira, Talita Maira Bueno da; Costa, Abel; Laks, Dani; Schaffel, Rony; et al. (Elsevier, 2025)
Chronic lymphocytic leukemia, characterized by an accumulation of monoclonal B lymphocytes, is the most common adult leukemia. The disease predominantly affects older adults, with a significant proportion being asymptomatic at diagnosis. This manuscript provides a comprehensive review of chronic lymphocytic leukemia, including its epidemiology, clinical presentation, diagnostic criteria, and treatment strategies. Prognostic factors, particularly IGHV mutation status and chromosomal abnormalities, are discussed as critical determinants of disease behavior and treatment response. Recent advances in targeted therapies, such as Bruton's tyrosine kinase inhibitors (BTKi) and B-cell lymphoma 2 inhibitors (BCL-2i), have changed the treatment landscape by demonstrating superior efficacy to chemoimmunotherapy. However, disparities in access to care, particularly in low- and middle-income countries such as Brazil, highlight the need for equitable treatment approaches. The discussion of measurable residual disease (MRD) assessment for prognostication and treatment planning is also highlighted. This review highlights the need for continued research and integration of novel therapies to optimize patient outcomes in chronic lymphocytic leukemia.